The Influence of the Board of Commissioners, Management Compensation, and Independent Commissioners on Tax Management - Laode Wijaya Bagus Irianto; Haliah; Nirwana (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to analyze the relationship between the board of commissioners, management compensation, and independent commissioners and tax management in companies. The research method used is an associative method by collecting data from public companies listed on the stock exchange. Statistical analysis was carried out using simple linear regression techniques to evaluate the relationship between the variables studied. The research results show that management compensation has a significant relationship with tax management practices, while the board of commissioners and independent commissioners also have a significant influence. The implications of these findings are discussed in the context of corporate management and tax policy.